The Story of Struggle and Hope: Narrative Accounts of Female STEM Students in Egyptian Higher Education - Tamer Youssef; Dina Ahmet; Yasser Sayed (Journal Emerging Technologies in Education, 2026)
Baground. Women in science, technology, engineering, and mathematics (STEM) fields in Egypt continue to face persistent structural and socio-cultural challenges, despite policy efforts to promote gender equity in higher education. The experiences of female STEM students remain underrepresented in scholarly discourse, particularly from an emic, narrative perspective. Purpose. This study aims to explore the lived experiences, challenges, and aspirations of female undergraduate STEM students in Egyptian universities through narrative inquiry.Method. Drawing on in-depth, semi-structured interviews with 20 participants from three major public institutions, the research documents personal accounts of gender-based obstacles, including societal expectations, institutional biases, and limited access to mentorship. Thematic narrative analysis revealed two dominant storylines: struggle against systemic barriers and hope grounded in academic identity, family support, and peer solidarity.Results. Findings reveal two dominant narrative arcs: “struggle”-characterized by marginalization, institutional neglect, and gender bias-and “hope”-rooted in academic identity, peer solidarity, and personal resilience. Participants employed strategies such as informal mentorship, emotional self-regulation, and counter-stereotypical performance to navigate male-dominated academic spaces.Conclusion. The study concludes that while structural inequalities persist, female students actively construct pathways of persistence, agency, and transformation within STEM fields. These findings provide valuable insights for educators, policymakers, and institutional leaders aiming to foster inclusive and supportive environments in STEM education.